HPV vaccine acceptability in HIV-infected and HIV negative men who have sex with men (MSM) in Ireland. Issue 6 (2nd June 2016) - Sadlier, C.; Lynam, A.; O'Dea, S.; Delamere, S.; Quinlan, M.; Clarke, S.; Sheils, O.; Bergin, C.
ABSTRACT: Background Men who have sex with men (MSM), particularly HIV-infected MSM are disproportionately affected by HPV infection and associated disease. The HPV vaccine has potential to greatly reduce the burden of HPV-associated disease including anal cancer in MSM. The efficacy of the HPV vaccine is dependent on high levels of vaccine uptake. The aim of this study was to examine HPV vaccine acceptability and factors influencing vaccine acceptability in MSM in Ireland.Methods A self-administered survey was distributed to HIV-infected and HIV negative MSM examining HPV vaccine acceptability and factors associated with vaccine acceptability. Logistic regression was used to identify key variables and predictors of HPV vaccine acceptability.Results 302 MSM participated in the study. Acceptability of HPV vaccine was 31% (unconditional), 51% (conditional on stated efficacy and a cost of €300), 65% (conditional on stated efficacy and a cost of €100) and 78% (conditional on stated efficacy and no cost). Cost was negatively associated with HPV vaccine acceptability (p<0.01) while knowledge of HPV vaccine efficacy was significantly associated with vaccine acceptability, even in the context of associated cost (p<0.01).Conclusions Acceptability of HPV vaccine in MSM in Ireland is high based on no cost vaccine and on stated vaccine efficacy (78%). Cost is negatively associated with vaccine acceptability. Understanding levels of knowledge of HPV infection, HPV associated disease and attitudes toward HPV vaccination are important as they will contribute to HPV vaccine acceptability among MSM and will help guide effective preventive programs.